Heterozygous HMGB1 loss‐of‐function variants are associated with developmental delay and microcephaly. Issue 4 (28th June 2021) - Uguen, Kévin; Krysiak, Kilannin; Audebert‐Bellanger, Séverine; Redon, Sylvia; Benech, Caroline; Viora‐Dupont, Eléonore; Tran Mau‐Them, Frederic; Rondeau, Sophie; Elsharkawi, Ibrahim; Granadillo, Jorge L.; Neidich, Julie; Soares, Celia Azevedo; et al.
Abstract: 13q12.3 microdeletion syndrome is a rare cause of syndromic intellectual disability. Identification and genetic characterization of patients with 13q12.3 microdeletion syndrome continues to expand the phenotypic spectrum associated with it. Previous studies identified four genes within the approximately 300 Kb minimal critical region including two candidate protein coding genes: KATNAL1 and HMGB1 . To date, no patients carrying a sequence‐level variant or a single gene deletion in HMGB1 or KATNAL1 have been described. Here we report six patients with loss‐of‐function variants involving HMGB1 and who had phenotypic features similar to the previously described 13q12.3 microdeletion syndrome cases. Common features included developmental delay, language delay, microcephaly, obesity and dysmorphic features. In silico analyses suggest that HMGB1 is likely to be intolerant to loss‐of‐function, and previous in vitro data are in line with the role of HMGB1 in neurodevelopment. These results strongly suggest that haploinsufficiency of the HMGB1 gene may play a critical role in the pathogenesis of the 13q12.3 microdeletion syndrome. Abstract :